2019
DOI: 10.1021/acsphotonics.8b01396
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Single Photons by Temporal Heralding of Quantum Dot Sources

Abstract: Efficient, high rate photon sources with high single photon purity are essential ingredients for quantum technologies. Single photon sources based on solid state emitters such as quantum dots are very advantageous for integrated photonic circuits, but they can suffer from a high two-photon emission probability, which in cases of non-cryogenic environment cannot be spectrally filtered. Here we propose two temporal purificationby-heralding methods for using a two photon emission process to yield highly pure and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…This high value of g (2) (0) is a result of the measurements being mainly done near saturation where both biexciton and plasmonic emission play a role (see Supplementary Information form more details). Using the time-filtered gating technique 38,41,42 we confirm that the emitter is indeed a single QD by measuring the second order coherence starting from various times (T F ) after the excitation pulse. This helps in differentiating between the emission of bi-excitons (which have shorter lifetime) and the emission of multiple QDs.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…This high value of g (2) (0) is a result of the measurements being mainly done near saturation where both biexciton and plasmonic emission play a role (see Supplementary Information form more details). Using the time-filtered gating technique 38,41,42 we confirm that the emitter is indeed a single QD by measuring the second order coherence starting from various times (T F ) after the excitation pulse. This helps in differentiating between the emission of bi-excitons (which have shorter lifetime) and the emission of multiple QDs.…”
mentioning
confidence: 78%
“…3f). Furthermore we recently proposed a new heralded scheme to overcome this limitation 42 where we propose two methods(in addition to the time gated method used here) which utilize the difference in lifetime between the biexciton and exciton states and/or the cascaded nature of the emission to separate the resulting two photon emission in time. Critically we have shown that the use of these methods lead to better efficiencies depending on the original biexciton and exciton quantum efficiencies.…”
mentioning
confidence: 99%
“…The methods and results presented in sections 3.2 and 3.3 provide a detailed picture of the time dynamics and quantum properties of imperfect photonic states. This can be used to optimize post-processing methods such as temporal filtering [254] to minimize the effect of pure dephasing and unwanted multi-photon noise on the desired state. The content of section 3.3 also provides a basis to study the effect of emitter imperfections on more complicated processes, such as photonic graph state generation for all-optical quantum repeaters [255].…”
Section: Discussionmentioning
confidence: 99%
“…The distinct rapidity of multiexciton emission allows for temporal filtering via post processing as shown in Figure 3d, e. The possibility of temporal filtering can be exploited to make such antennas better single photon sources [34]. As long as the exciton quantum yield of the QD is stable, the ant-enna emission can be switched very rapidly between single photon and multiphoton emission by varying the excitation intensity-this effect can find application in optoelectronic technologies [35].…”
Section: Single Photon Emission From Antennas Under Low Excitationmentioning
confidence: 99%